Extended T-Type Boost Inverter Using Switched Capacitors - Sugimoto, Tomoya; Nozaki, Takahiro; Murakami, Toshiyuki (IECON 2019 - 45th Annual Conference of the IEEE Industrial Electronics Society, 2019)
Recently, for renewable energy applications, multilevel inverters are an attractive option due to their advantages, such as harmonics reduction, low electromagnetic interferences, and small voltage stress. Additionally, lower DC-link voltage should be converted to higher AC voltage, which needs an inverter and a DC-DC boost converter or a transformer. However, the two-stage conversion reduces efficiency and reliability in renewable energy applications. Hence, a single-stage conversion system which can directly change the lower DC-link voltage to higher AC voltage is required. Some single-stage conversion systems have been proposed before. However, the maximum boost ratio and the level of these systems are constant, which limits applications. This paper proposes a multilevel boost inverter stepping up the AC output peak voltage at any boost ratio by changing the number of switched capacitors. The operation principle and the boost ability with multiple boost ratios are confirmed by simulations.